2005
DOI: 10.1177/1090198105276966
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Gun Use by California Adolescents

Abstract: Most research on adolescents and firearms focus on urban populations, handguns, and homicide. The present investigation examines the prevalence and correlates of recreational gun use (RGU) -for hunting or target shooting -among 5801 community-residing 12-to 17-year old Californians. Data are from the first statewide California Health Interview Survey (CHIS), and person, design, and population weights were applied to the data. About one-fifth (22.4%) of California adolescents report that they have gone hunting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The results of this study are consistent with findings from previous investigations of rural adolescent health indicating significant risk behaviors and health concerns among youth in the rural community 14,15,18–31 . Issues of particular concern include sexual health, substance use, mental health, and risk factors for obesity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are consistent with findings from previous investigations of rural adolescent health indicating significant risk behaviors and health concerns among youth in the rural community 14,15,18–31 . Issues of particular concern include sexual health, substance use, mental health, and risk factors for obesity.…”
Section: Discussionsupporting
confidence: 90%
“…In a comparison of rural and urban populations, Levine and Coupey 15 concluded that rural adolescents may be at greater risk for poor health outcomes related to a prevalence of health risks commensurate with a paucity of accessible community resources. Several studies have documented health risks in rural adolescent populations surpassing metropolitan statistics, including issues such as substance abuse, unsafe sexual practices, motor vehicle and other traumatic accidents, and interpersonal violence 18–30 . However, empirical data on rural adolescent populations remain limited 29–31 .…”
Section: Rural Adolescentsmentioning
confidence: 99%
“…More-restrictive minimum age laws could plausibly impact the gun industry by reducing the size of the consumer population and decreasing the ownership and use of guns by youth for hunting or recreational purposes. Overall, hunting participation in the United States has declined dramatically over the past decades, and although data on youth recreational firearm use are limited (Vittes and Sorenson, 2005), estimates from 2015 suggest that 1.8 million youth aged 6-15 engaged in hunting (U.S. . Furthermore, a large majority of adult hunters initiate hunting activities before age 20, and those who have not learned to hunt by age 20 have a very low likelihood of participating in hunting activities as an adult (Duda and Young, 1993).…”
Section: Minimum Age Requirementsmentioning
confidence: 99%
“…More-restrictive minimum age laws could plausibly impact the gun industry by reducing the size of the consumer population and decreasing the ownership and use of guns by youth for hunting or recreational purposes. Overall, hunting participation in the United States has declined dramatically over the past decades, and although data on youth recreational firearm use are limited (Vittes and Sorenson, 2005), estimates from 2015 suggest that 1.8 million youth aged 6-15 engaged in hunting (U.S. . Furthermore, a large majority of adult hunters initiate hunting activities before age 20, and those who have not learned to hunt by age 20 have a low likelihood of participating in hunting activities as an adult (Duda and Young, 1993).…”
Section: Minimum Age Requirementsmentioning
confidence: 99%